Identifikasi Mutasi Gen kelch 13 Penanda Resistensi Pada Plasmodium falciparum Dengan Pengobatan ACT Setelah 3 Hari Di Manokwari Papua Barat - Nesan, Sarlince Agustin; Santosa, Budi -; Kamarudin, Mudyawati (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Malaria is almost found all over the world, including Indonesia. WHO data on malaria case transmission in 2020, namely 241 million and 627,000 deaths. Female Anopheles mosquitoes are the main factor in the transmission of parasites, one of which is Plasmodium falciparum which is most dangerous to cause complications to death. Data from the Ministry of Health 2019 the highest transmission in Papua Province is 216,380 cases. The malaria elimination program uses ACT as a treatment therapy for malaria. The first appearance of ACT resistance in Cambodia was in 2008 to Plasmodium falciparum which was associated with the presence of a Kelch 13 gene mutation. The purpose of this study was to identify a mutation of the Kelch 13 gene markers of resistance in Plasmodium falciparum with ACT treatment after 3 days. This type of exploratory study used a population of all patients at the Amban Manokwari Health Center in West Papua, with a total sampling in August-September 2022. Of the 51 and 11 H3 samples met the inclusion criteria using RDT and Microscopic methods. The DNA isolated sample using Favorgen kit then amplified PCR and electrophoresis gel agarose. Then were 7 amplicons seen in the DNA band (±200bp) and confirmed results from PT. Science Genetics (±100bp), then 1 amplicon is continued for sequencing. The sequence results were analyzed using the Bioedit and Mega IX softwere with the alignment of the sequence results. Changes in nucleeid bases and amino acids were obtained so that the mutation of the Kelch 13 gene occurred, 3 mutation variants: substitution (transition & transversion), silent mutation (C3T codon 1 cysteine-cysteine), and missense mutation (T4A codon 2 tryptophan-serine). It can be concluded that the Plasmodium falciparum treatment ACT carriers the Kelch 13 gene mutation as one of the markers of resistance. Keywords: ACT, Plasmodium falciparum, Kelch 13 Gene Mutation.